Optimisation of multi-part production in additive manufacturing for reducing support waste. Issue 3 (3rd July 2019) - Jiang, Jingchao; Xu, Xun; Stringer, Jonathan
ABSTRACT: Additive manufacturing (AM) is becoming increasingly popular because of its unique advantages. However, AM still suffers from support material waste during the fabrication process when overhanging features exist. Plenty of research has been carried out for minimising support usage. However, former studies only focused on the optimisation for a single part fabrication. In this paper, a four-step strategy of multi-part production for reducing support consumption in AM is proposed. When printing a group of parts in the same build vat or chamber, the proposed strategy optimises the print orientation for each part, combines every two parts based on the geometries, proposes several possible multi-part combinations, and then selects the optimal part positions for fabrication. Two case studies are carried out for verification. The results show that the four-step strategy can significantly reduce the support waste and total fabrication time.